Magnetic nanoparticle bonding to PVC with the help of click reaction: characterization, thermal and electrical investigation - Tukur, Abdulrahman; Pekdemir, Mustafa Ersin; Haruna, Hassan; Coskun, Mehmet (Springer, 2020)
In this study the electrical properties of PVC have been improved. Thus, the copolymerization of methylmethacrylate and vinyltrimethoxysilane was performed by atom transfer radical polymerization (ATRP) using propargyl alpha-bromoisobutyrate, as initiator. Also, CuBr and 5.5 '-dimethyl-2.2 '-dipyridyl (mbpy) was used as the catalyst, and then, the magnetic nanoparticle was bonded to vinyltrimethoxysilane units of the copolymer. Through the click reaction method, PVC containing about 10% azido group was bonded with the copolymer that contained propargyl end group bearing the magnetic nanoparticles in the side chain. FT-IR, H-1 and C-13 NMR, SEM-EDX and SEM techniques were used in the characterization. Thermal analysis showed that the thermal stability of azido functionalized PVC was decreased compared with PVC, and increased after grafting of the magnetic nanoparticle bounded with copolymer. The vibrating sample magnetometer (VSM) measurements illustrated that the saturation magnetics of the product was 41.5 emu/g and the initial magnetic susceptibility (chi(i)) value was 0.034 emu/g.Oe. Consequently, these values showed that the product was superparamagnetic. Variation of dielectric constant with frequency and variation of AC conductivity with frequency at four different temperatures were also investigated. The activation energy of the conductivity was calculated as 0.139-0.134 eV in the 500-10,000 Hz frequency range.
Keywords: PVC; Click chemistry; Magnetic nanoparticle; Dielectric; Thermal